Are Fc Gamma Receptor Polymorphisms Important in HIV-1 Infection Outcomes and Latent Reservoir Size? - Lamptey, Helena; Bonney, Evelyn Y.; Adu, Bright; Kyei, George B. (Frontiers in Immunology, 2021)
Fc gamma receptors (FcγR) are cell surface glycoproteins which trigger specific effector-cell responses when cross-linked with the Fc portions of immunoglobulin (IgG) antibodies. During HIV-1 infection, the course of disease progression, ART response, and viral reservoir size vary in different individuals. Several factors may account for these differences; however, Fc gamma receptor gene polymorphisms, which influence receptor binding to IgG antibodies, are likely to play a key role. FcγRIIa (CD32) was recently reported as a potential marker for latent HIV reservoir, however, this assertion is still inconclusive. Whether FcγR polymorphisms influence the size of the viral reservoir, remains an important question in HIV cure studies. In addition, potential cure or viral suppression methods such as broadly neutralizing antibody (bNAbs) may depend on FcγRs to control the virus. Here, we discuss the current evidence on the potential role played by FcγR polymorphisms in HIV-1 infection, treatment and vaccine trial outcomes. Importantly, we highlight contrasting findings that may be due to multiple factors and the relatively limited data from African populations. We recommend further studies especially in sub-Saharan Africa to confirm the role of FcγRIIa in the establishment of latent reservoir and to determine their influence in therapies involving bNAbs.